PENDIDIKAN POLITIK PEMILIH PEMULA SEBAGAI BAGIAN INDIKATOR PEMILU BERKUALITAS - Hasyim, Abdulloh (SIYASI: Jurnal Trias Politica, 2023)
Implementation of law number 2 of 2008 concerning political parties regarding political education for first-time voters in the 2024. General election the importance of political education for first-time voters in the 2024 general election is to become intelligent voters and understand the political dynamics that are occurring. This research aims to find out how political education is implemented for novice voters. How is the participation of novice voters in carrying out the 2024. General election. This research uses normative legal methods. Data collection techniques use literature study. Data was tested by source triangulation. Data analysis techniques go through the stages of data collection, data reduction, data presentation, and drawing conclusionsImplementasi undang-undang nomor 2 tahun 2008 tentang partai politik terhadap pendidikan politik untuk pemilih pemula dalam pemilihan umum 2024. Pentingnya pendidikan politik pemilih pemula dalam pemilihan umum 2024 agar menjadi pemilih yang cerdas serta memahami situasi serta kondisi politik yang terjadi sekarang ini. Penelitian ini bertujuan untuk mengetahui, Bagaimana Impelemntasi pendidikan politik terhadap pemilih pemula. serta Bagaiaman partisipasi pemilih pemula dalam melaksanakan pemilihan umum 2024. Penelitian ini mengunakan metode hukum normatif Teknik pengumpulan data menggunakan Studi Kepustakaan. Teknik analisis data melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan